2013
DOI: 10.3851/imp2674
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Pharmacokinetic Interactions of the HCV Ns5A Replication Complex Inhibitor Daclatasvir with Antiretroviral Agents: Ritonavir-Boosted Atazanavir, Efavirenz and Tenofovir

Abstract: The pharmacokinetic data support coadministration of daclatasvir with atazanavir/ritonavir, efavirenz and/or tenofovir. A Phase III study in HIV-HCV coinfection has commenced using the described dose modifications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 34 publications
2
75
0
Order By: Relevance
“…), a 90 mg dose of DCV has been recommended. 22 When used with potent CYP3A4 inhibitors (e.g. ritonavir-boosted atazanavir), a 30 mg dose of DCV has been recommended.…”
Section: Daclatasvir (Dcv)mentioning
confidence: 99%
See 1 more Smart Citation
“…), a 90 mg dose of DCV has been recommended. 22 When used with potent CYP3A4 inhibitors (e.g. ritonavir-boosted atazanavir), a 30 mg dose of DCV has been recommended.…”
Section: Daclatasvir (Dcv)mentioning
confidence: 99%
“…On the other hand, DCV dose needs to be increased to 90 mg when it is administered with inducers of CYP3A4 (efavirenz and etravirine). 22 The safety and efficacy of DCV and SOF therapy in HCV and HIV coinfection has been shown in the ALLY-2 trial, which had evaluated a 12-week vs. 8-week regimen in GT-1 to 4 in treatment-naive (n = 151) and treatment-experienced (n = 52) HIV and HCV coinfected patients. The study showed a SVR at 12 weeks (SVR12) of 96% with 12-week combination therapy, but in case of 8-week therapy, the SVR12 was only 76%.…”
Section: Management Of Hcv In Hiv Coinfectionmentioning
confidence: 99%
“…Ritonavirboosted atazanavir increased DCV AUC by 2.1-fold, whereas efavirenz reduced DCV AUC by 32%. DCV dose modification from 60 mg to 30 mg with ritonavir-boosted atazanavir and 90 mg with efavirenz were predicted to normalize AUC relative to the target exposure [23,24]. No interaction was observed with TDF [24].…”
Section: Daclatasvirmentioning
confidence: 99%
“…DCV dose modification from 60 mg to 30 mg with ritonavir-boosted atazanavir and 90 mg with efavirenz were predicted to normalize AUC relative to the target exposure [23,24]. No interaction was observed with TDF [24]. A DCV dose reduction to 30 mg was assumed to be appropriate for other ritonavir-boosted protease inhibitors given the interaction observed with ritonavir-boosted atazanavir.…”
Section: Daclatasvirmentioning
confidence: 99%
“…47,48 DCV was recently approved in the United States; DCV has been available in the European Union with guidelines for its use in patients with HIV coinfection. 49 Efficacy data from a phase III trial (ALLY-2, NCT02032888) in coinfected patients show excellent response rates in this population in line with other HCV monoinfected and coinfected data for SOF plus an NS5A inhibitor.…”
Section: Wylesmentioning
confidence: 99%